Low nocturnal temperature changed protected tomato soil bacterial community composition and metabolite characteristics - Qingwen Shi; Zhouping Sun; Hongdan Fu; Yufeng Liu; Tianlai Li (Biology and Fertility of Soils, 2026)

Synergistic in situ growth and interfacial modification of ZIF-8@PDMS membranes for efficient DMC/methanol separation - Qing Zeng; Zhihui Zhou; Hongdan Wu; Wenming Fu; Xianyuan Fan; Guoyuan Lei; Junlin Peng (Journal of Environmental Chemical Engineering, 2026)

α-Amanitin aggravates hepatic injury by activating oxidative stress and mitophagy via peroxiredoxin 6 inhibition - Zhongfeng Cheng; Kerun Cheng; Yan Tang; Xueqiong Duan; Yangshan Fu; Hongdan Duan; Yong Ye (Immunologic Research, 2025)

Keystone ecological cluster rather than the whole community of phoD-encoding bacteria driving ecological function and the improvement of yield under long-term organic regime in greenhouse - Xiaoxia Li; Pengjie Li; Muhammad Awais; Zhu Zhang; Shuning Zhao; Yufeng Liu; Zhouping Sun; Hongdan Fu; Tianlai Li (Agriculture, Ecosystems & Environment, 2025)

Microorganisms regulate soil phosphorus fractions in response to low nocturnal temperature by altering the abundance and composition of the pqqC gene rather than that of the phoD gene - Qingwen Shi; Qiaobo Song; Xuan Shan; Xiaoxia Li; Shuang Wang; Hongdan Fu; Zhouping Sun; Yufeng Liu; Tianlai Li (Biology and Fertility of Soils, 2023)

Fabrication and application of molecularly imprinted polymer doped carbon dots coated silica stationary phase - Peijun Chai; Xuhui Geng; Ruirui Zhu; Wenpu Wu; Xuesong Wang; Jinhua Li; Longwen Fu; Hongdan Wang; Wanhui Liu; Lingxin Chen; Zhihua Song (Analytica Chimica Acta, 2023)

Study of the LQRY-SMC Control Method for the Longitudinal Motion of Fully Submerged Hydrofoil Crafts - Hongdan Liu; Yunxing Fu; Bing Li (Journal of Marine Science and Engineering, 2022)
The control system is one of the important components of the hydrofoil craft. By adjusting the navigation attitude of the craft, the hydrofoil craft can navigate stably and safely in the turbulent environment. Aiming at the problem that existing control algorithms have poor stability in the longitudinal motion control of hydrofoil craft, the longitudinal motion reduction is limited, and there are excessive requirements for accurate disturbance wave data. Based on the fully submerged hydrofoil craft model, this article proposes a joint control method LQRY-SMC combining linear-quadratic optimal control with output regulation (LQRY) and sliding-mode control (SMC), and adds genetic algorithm to optimize the weighting matrix parameters, get better control-feedback gain, improve the global optimal-control stability, thus improving the comfort of the crew, and prevent the attack of the hull, deck wetness and damage to instruments. The simulation results show that compared with the existing methods, the heave displacement and pitch angle obtained by LQRY-SMC under the turbulent flow of different significant wave heights are reduced by about 50%, and the influence of longitudinal motion on hydrofoil crafts is avoided to a large extent, which proves the effectiveness and superiority of the method proposed.